PENGARUH MODEL COOPERATIVE LEARNING BERBANTUAN MEDIA WORDWALL TERHADAP PENINGKATAN PEMAHAMAN BELAJAR DAN KOLABORASI SISWA SEKOLAH DASAR - Eneng Endah; Uum Murfiah; Jaka Permana (PT. Hasba Edukasi Mandiri, 2025)
This research was motivated by the low level of students' learning comprehension and collaboration in IPAS subjects, caused by a lack of learning enthusiasm, interest, and active involvement because learning was still teacher-centered. The aim of this study was to examine the effect of the Cooperative Learning model of the Teams Games Tournament (TGT) type assisted by Wordwall media on improving learning comprehension and collaboration in IPAS for Grade IV students in the 2025/2026 academic year. The research used a quantitative method with a quasi-experimental design. The subjects of this study were all Grade IV students at SD Negeri Cijagra 04 for the 2025/2026 academic year. The sample consisted of 29 students in Grade IV A as the experimental class and 29 students as the control class. Data collection techniques included multiple-choice tests on the life cycle of living animals and observation sheets as supporting data. The tests were conducted using pretests and posttests to measure students' learning comprehension. Data analysis techniques included validity tests, reliability tests, difficulty level analysis, and discrimination index analysis. The experimental class scored 69.52 on the pretest, which increased to 79.86 on the posttest. Meanwhile, the control class scored 66.10 on the pretest and 66.86 on the posttest. The independent t-test results showed a significant value, with a t-count of 6.428 and a Sig. (2-tailed) value of 0.001, which is smaller than 0.05. This means that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The TGT cooperative learning model had a large effect on learning comprehension, indicated by an effect size of 1.71 (large category). Based on the frequency distribution of overall collaboration scores in meetings 1 and 2: teamwork 55.2% vs 10.3%, communication 62.1% vs 6.9%, positive interdependence 48.3% vs 6.9%, and social responsiveness 55.2% vs 10.3%. The n-Gain of the experimental class was 0.3194 (moderate category), while the control class was 0.0232 (low category). Therefore, it can be concluded that the cooperative learning model of the Teams Games Tournament (TGT) type assisted by Wordwall media significantly affected the improvement of IPAS learning comprehension and collaboration in Grade IV students.